HARDWARE AND SOFTWARE SOLUTIONS FOR THE PROTECTION OF PERSONALLY IDENTIFIABLE DATA IN TELECOMMUNICATION SYSTEMS AND NETWORKS - RUDYI, ROMAN; VOROBETS, HEORHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article presents a comprehensive study of hardware and software solutions aimed at securing personally identifiable information within modern telecommunication systems and networks. The increasing integration of digital technologies into all aspects of life—from healthcare and education to government administration—has intensified the demand for reliable and scalable data protection mechanisms.  The paper categorizes and analyzes hardware-based security solutions such as hardware encryption modules, secure enclaves, security tokens, and the E-LUKS encryption system, emphasizing their efficiency in providing physical isolation and cryptographic protection. These methods are particularly effective in environments with constrained resources, such as IoT devices, where traditional security measures may be impractical. The article also explores biometric authentication mechanisms, which enhance data security through the use of unique biological identifiers such as fingerprints and facial recognition. On the software side, the study details solutions including encryption algorithms, data compression technologies, authentication and authorization systems, intrusion detection systems (IDS), firewalls, and secure cloud services. It highlights the adaptive capabilities of software measures in responding to rapidly evolving threats and managing access policies in virtualized or distributed environments.  The article concludes that neither hardware nor software security approaches are sufficient on their own. Instead, a hybrid security model that combines both is necessary for effective defense against modern cybersecurity challenges. This integrated approach ensures data confidentiality, integrity, and availability while supporting scalability and operational resilience. Recommendations are made for deploying layered security architectures that utilize the strengths of both hardware and software mechanisms to protect personal data in contemporary telecommunications infrastructure.
Keywords: hardware solutions; software solutions; telecommunication systems and networks; encryption